2011
DOI: 10.1371/journal.pone.0026300
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Phosphatidylinositol 4-Kinase PI4KA in Hepatitis C Virus-Induced Host Membrane Rearrangement

Abstract: BackgroundHepatitis C virus (HCV), like other positive-sense RNA viruses, replicates on an altered host membrane compartment that has been called the “membranous web.” The mechanisms by which the membranous web are formed from cellular membranes are poorly understood. Several recent RNA interference screens have demonstrated a critical role for the host phosphatidylinositol 4-kinase PI4KA in HCV replication. We have sought to define the function of PI4KA in viral replication.Methodology/Principal FindingsUsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
100
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 40 publications
6
100
0
Order By: Relevance
“…These studies offered new possibilities to counter the establishment of viral replication machinery using PI4K inhibitors. The important feature of these studies was that viral replication was almost completely abolished by even partial PI4K knockdown, which elicited no apparent cellular toxicity in vitro (21). These findings have confirmed our previous conclusions that even small amounts of the enzyme can fulfill its "housekeeping" functions (9).…”
supporting
confidence: 86%
“…These studies offered new possibilities to counter the establishment of viral replication machinery using PI4K inhibitors. The important feature of these studies was that viral replication was almost completely abolished by even partial PI4K knockdown, which elicited no apparent cellular toxicity in vitro (21). These findings have confirmed our previous conclusions that even small amounts of the enzyme can fulfill its "housekeeping" functions (9).…”
supporting
confidence: 86%
“…Similar to enteroviruses, the flavivirus Hepatitis C virus (HCV) requires PI4P lipids for replication, which are generated via the recruitment of PI4KIIIα [46][47][48][49][50][51][52][53]. West Nile virus attracts the cholesterol-synthesizing enzyme 3-HMGA-CoA reductase to replication sites [54,55], while dengue virus recruits fatty acid synthase and stimulates its activity [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…siRNA screening for host factors has revealed that PI4Ks are essential for HCV proliferation (28). Because the ER-localized PI4 kinase PI4KIII␣ has been shown to be important for viral induced membrane rearrangement and HCV replication, we primarily focused on investigating the role of Golgi-localized PI4P pools (30,31). We took advantage of Golgi-specific hSac1 K2A phosphatase to specifically deplete PI4P from the TGN.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these kinases, PI4KII␣ and PI4KIII␤, localize to the Golgi complex; however, PI4KIII␤ plays a more dominant role in maintaining important functional and structural attributes of the Golgi complex (29). It was recently shown that HCV induces enrichment of PI4P pools near the ER by PI4KIII␣ to trigger host membrane rearrangement required for HCV replication (30,31).…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
See 1 more Smart Citation